THE ROLE OF INTERDISCIPLINARY COMMUNICATION IN TEACHING PHYSICS - Ashirov Shamshidin Annazarovich (American Journals Publishing, 2023)
This article will talk about the important role of interdisciplinary communication in teaching physics. Physics, a multidisciplinary specialty, requires effective communication between different disciplines to increase students ' understanding and appreciation of its concepts. Raising the gap between physics and other sciences, interdisciplinary dialogue illuminates real-world programs and shapes critical thinking, problem-solving skills, collaboration, and teamwork. This article highlights the importance of integrating interdisciplinary approaches in physics education to give students a holistic understanding and prepare them for the complexities of the scientific challenges they may face in their future endeavors.